Cholinergic control of heart rate by nitric oxide is site specific. - Herring, N; Danson, E; Paterson, D (2002)
Parasympathetic control of heart rate involves the exocytotic release of acetylcholine and muscarinic receptor regulation of pacemaking currents. Endogenous nitric oxide can potentially regulate all of these processes; however, recent work suggests that the main functional role of nitric oxide lies in the modulation of acetylcholine release.